Phenolic compounds of Iris adriatica and their antimycobacterial effects - Ochensberger Sandra; Alperth Fabian; Mitić Božena; Kunert Olaf; Mayer Stefanie; Mourão Maria Ferreira; Turek Ivana; Luca Simon Vlad; Skalicka-Woźniak Krystyna; Maleš Željan; Hruševar Dario; Duka Ivan; et al. (Acta Pharmaceutica)
Little is known about the pharmacological activities of Iris adriatica (Iridaceae), a plant endemic to Dalmatia (Croatia). We therefore performed a bioassay-guided fractionation including high-performance counter current chromatography (HPCCC) and antibacterial tests using Mycobacterium smegmatis mc2 155. One obtained fraction was found to be antimycobacterially active with a MIC of 64 mg L−1. Furthermore, fractions were tested for resistance modulatory effects using ethidium bromide as substrate. We were able to identify the pure isoflavonic compounds irigenin and irilone and a fraction containing mainly benzophenone 2,4,6-trihydroxy-4-methoxy-benzophenone, responsible for the resistance-modulatory activity of this plant.